2020
DOI: 10.1111/ijfs.14629
|View full text |Cite
|
Sign up to set email alerts
|

Prosopis spp. powder: influence of chemical components in water adsorption properties

Abstract: Prosopis alba and Prosopis nigra powders from pods were evaluated through chemical and mineral composition and other healthy food compounds such as polyphenols and fatty acids exhibiting antioxidant activity. P. nigra presented higher content of lipids and polyphenols leading to a higher antioxidant activity than P. alba. Although P. nigra presented lower amount (%) of fibre (20.1 vs. 23.3), the amount of total soluble sugars responsible of water retention was slightly higher (PN: 57.1, PA: 56.7). Moisture con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Regarding Prosopis , the protein value range is also variable between species. In P. africana dehulled flour, the protein is in the range of 23 and 25.8% [ 33 ], closer to the value obtained in MF; meanwhile, in P. alba and P. nigra , the protein concentration is about 8% [ 34 ].…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Regarding Prosopis , the protein value range is also variable between species. In P. africana dehulled flour, the protein is in the range of 23 and 25.8% [ 33 ], closer to the value obtained in MF; meanwhile, in P. alba and P. nigra , the protein concentration is about 8% [ 34 ].…”
Section: Resultsmentioning
confidence: 94%
“…Brizzolari et al [ 48 ] reported a total phenolic content of 15.3 mg GA eq/kg for mesquite and antioxidant activity of 115 mmol TE/kg (FRAP assay). In P. alba and P. nigra species, the total phenolic content was reported between 625–1150 mg GA eq/kg, and antioxidant activity was reported between 5.4 and 10.02 µmol TE/100 g sample (by ABTS ± ) [ 34 ]. In P. chilensis and P. cineraria , the polyphenol content ranged from 0.82–2.57 g GA equivalent/100 g and 0.21–13.59 mg GA equivalent/100 g, respectively [ 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…The GAB model was also the one that best fit the sorption SMITH isotherms of [42] in a study of pure orange juice in spray-dried powder form. According to [43], the GAB model is also the most appropriate theoretical isotherm equation because the physical parameters included in the equation are highly important for material analysis.…”
Section: Water Sorption Isothermmentioning
confidence: 99%
“…The monolayer moisture content ( X m ) determined from moisture sorption isotherms has been a valuable tool for evaluating hygroscopicity behaviour and predicting the storage stability of dried food systems. The X m value is defined as the amount of water strongly absorbed to the active site on the food surface and considered as the safe moisture for powders during preservation (Stępien et al ., 2020; Sciammaro et al ., 2021). The a w is a solvent property defined as the ratio of the vapour pressure of water above the food to the vapour pressure of pure water at a constant temperature strongly dependent on the composition, water content and physical state of the compounds (Rahman et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%